3D finite element model of dynamic material behaviors for multilayer ultrasonic metal welding. (February 2021) - Shen, Ninggang; Samanta, Avik; Cai, Wayne W.; Rinker, Teresa; Carlson, Blair; Ding, Hongtao
Abstract: Ultrasonic metal welding (UMW) has been widely applied as a high throughput solid-state joining technology for multilayers of sheet metal. During a typical UMW process, multilayer work materials are mechanically compressed by a knurl-patterned horn (also known as a sonotrode) onto an anvil tool, and a simultaneous in-plane sliding is applied to the horn at an ultrasonic frequency (20 kHz or higher) to help form the weld at the material interfaces. There is a great challenge in modeling and simulating the dynamic behavior of the work material and the whole weld formation process is subject to ultrasonic mechanical loadings imposed by the knurl-patterned horn tool. In this work, finite element (FE) models are developed to simulate the multilayer UMW process using knurl-patterned tools by directly applying the ultrasonic vibration as a model input. For a short weld duration of 0.1∼0.5 s, a high-fidelity FE modeling approach is developed using ABAQUS/Explicit to simulate the dynamic material response under the 20 kHz horn vibration. For an extended long welding duration of approximately 1.0 s, a computationally efficient hybrid approach is developed using both ABAQUS/Explicit and DEFORM-3D in order to leverage the strengths of each software package. The developed models are validated using experimental data of dynamic welding force, temperature, and weld geometry from in-situ process measurements of UMW. The 3D FE models developed in this study are the most comprehensive solution to date to simulate the complex material response subject to UMW process conditions and provide engineering guidance for the design of UMW applications.